Role of ultrasound guided epidural anesthesia for lower limb surgery in children with previously repaired meningomyelocele. Issue 3 (28th December 2017) - Ponde, Vrushali C.; Bedekar, Vinit V.; Chavan, Dilip; Gursale, Anuya; Shah, Dipal
Summary: Background: Children that have had a meningomyelocele repair often present for hip and bilateral lower limb surgeries. Due to vertebral, epidural, and nerve root abnormalities, placement of epidural catheter is difficult. Aims: We aim to describe the potential role of ultrasound in delineating the most appropriate intervertebral space for central neuroaxial blocks in these patients. Methods: Twelve children with previous meningomyelocele repair, in the age group of 6‐12 years posted for hip or bilateral lower limb surgeries were included. After induction of anesthesia, an ultrasound scan was done with the patient in the left lateral position. The central neuroaxial block was performed in the most appropriate intervertebral space seen on transverse scan of spine. These patients were studied with regard to visibility of the osseous framework of the spine, the anterior and posterior dural complexes, ease of insertion of catheter, evidence of dural puncture, and possibility of identification of the extent of peri‐incisional fibrosis. Results: One case required 2 attempts. There was no evidence of dural puncture. We could confirm the soft tissue shadow, the osseous framework, and the anterior and posterior dural complexes in all 12 patients. Ultrasonography guided in selecting the most appropriate space for epidural catheter placement. Conclusion: Ultrasound guidance aids in identification of normal intervertebral space and explicitly shows the abnormal space. It can be used as an aid to differentiate between normal and abnormal space in post‐meningomyelocele repair.